Diagnosis of Growth Hormone Deficiency is Affected by Calibrators Used in GH Immunoassays - Meazza, C.; Albertini, R.; Pagani, S.; Sessa, N.; Laarej, K.; Falcone, R.; Bozzola, E.; Calcaterra, V.; Bozzola, M. (Hormone and Metabolic Research, 2012)
Growth hormone (GH) values vary among immunoassays depending on different factors, such as the assay method used, specificity of antibodies, matrix difference between standards and samples, and interference with endogenous GH binding proteins (GHBPs). We evaluated whether the use of different calibrators for GH measurement may affect GH values and, consequently, the formulation of GH deficiency (GHD) diagnosis in children. Twenty-three short children (5 F, 18 M; age 11.4±3.1 years), with the clinical characteristics of GHD (height:  − 2.3±0.5 SDS; height velocity  − 2.3±1.5 SDS; IGF-I  − 1.2±0.9 SDS), underwent GH stimulation tests to confirm the clinical diagnosis of GHD. Serum GH values were measured with Immulite 2000, using 2 different calibrators, IS 98/574, a recombinant 22 kDa molecule of more than 95% purity, and IS 80/505, of pituitary origin and resembling a variety of GH isoforms. We found blunted GH secretion in 20 subjects with the Immulite assay using the IS 98/574 GH as a calibrator, confirming the diagnosis of GHD. Subsequently, using IS 80/505 GH as a calibrator, in the same samples only 14 children showed reduced GH levels. The total cost for the first year of GH therapy of patients diagnosed with IS 98/574 as a calibrator was higher than that for patients diagnosed with IS 80/505 as a calibrator. These data confirm that GH values may depend on different calibrators used in the GH assay, affecting the formulation of GHD diagnosis and the consequent decision to start GH treatment.
Keywords: growth hormone; chemiluminescent assay; calibrator; growth hormone deficiency; children